1999
DOI: 10.1111/j.1751-1097.1999.tb05302.x
|View full text |Cite
|
Sign up to set email alerts
|

Diel Cycles of DNA Damage and Repair in Eggs and Larvae of Northern Anchovy, Engraulis mordax, Exposed to Solar Ultraviolet Radiation

Abstract: Damage from UVB radiation (280-320 nm) in the form of cyclobutane pyrimidine dimers (CPD) in DNA and the capacity for their repair were measured in newly spawned eggs and yolk-sac larvae of northern anchovy, Engraulis mordax, exposed to natural diel cycles of sunlight. The CPD were measured by a newly developed chemiluminescent immunoblot assay capable of measuring CPD in samples as small as 50 ng DNA. Eggs and yolk-sac larvae exposed to full irradiance levels died. At lower dose rates, equivalent to deeper mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 27 publications
4
50
1
Order By: Relevance
“…reported on DNA photorepair in UV-B exposed platyfish Xiphophorus variatus and Mitani et al (1996) observed that exposure to UV-A and blue light induced the production of cyclobutane pyrimidine dimer photolyase (involved in the repair of UV-Binduced DNA damage) in cultured cells of the goldfish Carassius auratus. Similar results on photorepair have been reported by Vetter et al (1999 (Vetter et al 1999). …”
Section: Outdoor Exposure Experimentssupporting
confidence: 80%
See 3 more Smart Citations
“…reported on DNA photorepair in UV-B exposed platyfish Xiphophorus variatus and Mitani et al (1996) observed that exposure to UV-A and blue light induced the production of cyclobutane pyrimidine dimer photolyase (involved in the repair of UV-Binduced DNA damage) in cultured cells of the goldfish Carassius auratus. Similar results on photorepair have been reported by Vetter et al (1999 (Vetter et al 1999). …”
Section: Outdoor Exposure Experimentssupporting
confidence: 80%
“…Remediating effects of photorepair on UV-B-induced mortality, and DNA damage, have been reported for northern anchovy Engraulis mordax larvae (Kaup & Hunter 1981, Vetter et al 1999. reported on DNA photorepair in UV-B exposed platyfish Xiphophorus variatus and Mitani et al (1996) observed that exposure to UV-A and blue light induced the production of cyclobutane pyrimidine dimer photolyase (involved in the repair of UV-Binduced DNA damage) in cultured cells of the goldfish Carassius auratus.…”
Section: Outdoor Exposure Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these species, DNA-damage and repair are simultaneous processes and UVB-induced cyclobutane pyrimidine dimers (CPDs) are repaired very rapidly within one day. This is also the case for northern anchovy eggs and larvae, where UV-induced DNA-damage (CPDs) and photoenzymatic repair happen very fast (within hours) and the daily cycle of UVR damage and photorepair follow the solar intensity, with a peak in CPD accumulation at noon, followed by a decline in CPD content until sunset, due to photorepair (Vetter et al, 1999). Dark repair during low light recovery phases in our experiments could explain oxygen consumption, 200% elevated over initial non-stressed rates.…”
Section: Metabolic Rate and Response To Uvr-exposurementioning
confidence: 99%